Bridging the academia-practitioner divide: the case of "service theater". Issue 7 (7th October 2014) - Daly, Aidan; Baron, Steve; J. Dorsch, Michael; P. Fisk, Raymond; J. Grove, Stephen; Harris, Kim; Harris, Richard
Abstract : Purpose: – This paper aims to demonstrate the applicability of a theatrical framework for improving the effectiveness of the knowledge transfer of service research findings to practitioners. Design/methodology/approach: – A case study approach is adopted. The operation of a practitioner-oriented seminar is examined through a theatrical lens to establish the extent to which direction, audience participation and creativity, emotions and visual aesthetics can contribute to bridging the academia-practitioner divide. Findings: – Planning a practitioner-oriented seminar performance is as important as planning the program content. Effective knowledge transfer requires active audience engagement, activation of favorable audience emotions and an enjoyable learning process. The lack of these requirements can render written dissemination by journal papers relatively ineffective in reaching and engaging practitioners. Research limitations/implications: – Findings are based on one case study: a seminar delivered to practitioners on "service theater". Practical implications: – In addition to face-to-face seminars, contemporary dissemination methods (webinars, podcasts) can apply the theatrical lessons introduced and evaluated. Practitioners do not respond positively to only written declarative information, through academic papers and/or PowerPoint slides, from academicians. Originality/value: – The article recognizes that dissemination of service research findings is, itself, a service, requiring depth of thought and understanding.